1
$\begingroup$

I would like to know how to prove that:

$$\psi^{(n)}(z)=(-1)^{n+1}n! \sum_{k=0}^{\infty}\frac{1}{\left ( k+z \right )^{n+1}}$$

I know that $\displaystyle \sum_{n=0}^{\infty}\frac{1}{n+z}=-\psi (z)$ but despite the differentiation I apply I cannot get the result . I get the alternating term but not the factorial.

$\endgroup$
  • $\begingroup$ Try differentiating it a few times, try to see the pattern. $\endgroup$ – Akiva Weinberger Feb 18 '15 at 11:21
  • $\begingroup$ That should read $\displaystyle \sum_{n={\color{red}{-\infty}}}^{\infty}\frac{1}{n+z}=-\psi (z)$, since $\displaystyle \sum_{n=0}^{\infty}\frac{1}{n+z}$ diverges $($obviously$)$. $\endgroup$ – Lucian Feb 18 '15 at 12:31
1
$\begingroup$

For $f(z)=\frac{1}{k+z}$ you have $f'(z) = - \frac{1}{(k+z)^2}, f''(z) = - (-2) \frac{1}{(k+z)^3}, - (-2) (-3) \frac{1}{(k+z)^4}, ...$.

From $\frac{1}{k+z} = \frac{1}{k}(1-\frac{z}{k}+(\frac{z}{k})^2+(\frac{z}{k})^3-...)= \sum_{i=0}^\infty \frac{1}{i!}(\frac{1}{k+z})^{(i)}z^i$ you obtain the result ($(i)$ means i-th derivative by $z$).

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.